Impact of using podcasts on students learning motivation - Irmadel Aurelliana; Syifa Syahfiana Nugraha (Universitas Pendidikan Indonesia, 2022)
A podcast is a media file or digital audio to be specific, which can be published regularly through the internet in a particular format, such as mp3 formats. Podcast is also widely used, and the education field is not an exception. During the pandemic state that is happening right now, the education process is required to continue, so a Distance Learning policy is issued, which requires all people, including students, to stay at home as a way to prevent transmission of the virus through a circular by the Minister of Education and Culture that stated in law number 3 of 2020 regarding the prevention of Covid-19. This distance learning policy requires educators to be able to choose suitable learning media. In this research, the researcher uses an interview method with the Mahad Abu Aziz elementary school teacher. The results showed that podcasts as a learning media received a good response from the students. Podcasts can be effectively used in the learning process only if the educators have good speaking ability, including good intonation, and can create a pleasant situation in their audio presentation. In conclusion, podcast as a learning media receives excellent feedback from students because it is considered easy to use and works better, especially in Language lesson. Abstrak Podcast adalah file media atau audio digital secara lebih spesifik, yang dapat dipublikasikan secara berkala melalui jaringan internet dalam format tertentu seperti format mp3. Podcast digunakan secara luas dan tidak terkecuali dalam bidang pendidikan. Dalam keadaan pandemi yang terjadi saat ini, proses pendidikan dituntut untuk tetap berjalan sehingga kebijakan Pembelajaran Jarak Jauh (PJJ) yang mewajibkan seluruh masyarakat termasuk pelajar untuk tetap berada di rumah sebagai cara pencegahan penularan virus dikeluarkan melalui surat edaran oleh Menteri Pendidikan dan Kebudayaan yang tertuang dalam Undang-undang Nomor 3 tahun 2020 tentang pencegahan Covid-19. Kebijakan pembelajaran jarak jauh ini menuntut para pendidik untuk dapat memilih media pembelajaran yang tepat. Dalam penelitian ini, peneliti menggunakan metode wawancara kepada guru di sekolah dasar Mahad Abu Aziz. Hasil penelitian menunjukkan bahwa penggunaan podcast sebagai media pembelajaran mendapat respon yang baik dari peserta didik. Podcast dapat digunakan secara efektif dalam proses pembelajaran hanya jika pendidik memiliki kemampuan berbicara yang mumpuni termasuk penggunaan intonasi yang baik serta mampu menciptakan situasi yang menyenangkan dalam presentasi audio mereka. Kesimpulannya, podcast sebagai media pembelajaran mendapat tanggapan yang sangat baik dari peserta didik karena dianggap mudah digunakan dan berjalan dengan baik terutama apabila digunakan dalam pelajaran Bahasa. Kata Kunci: Media pembelajaran; motivasi belajar; pembelajaran jarak jauh; podcast